Política nacional de resíduos sólidos: uma análise nos municípios que integram o Corede Vale do Jaguari, RS - Leal Neto, Heitor Soares (2023)
This study aimed to identify the municipalities that are part of Corede Vale do Jaguari and is applying the existing definitions in the National Solid Waste Policy - PNRS, issuing evidence such as actions related to selective collection, landfills, composting plants, reverse logistics, formation of associations and cooperatives and solid waste management plans. The work was focused on identifying existing actions in the cities of Cacequi, Capão do Cipó, Jaguari, Mata, Nova Esperança do Sul, Santiago, São Francisco de Assis, São Vicente do Sul and Unistalda, as well as the needs presented, citing the good practices already in operation. The theoretical foundation addresses Public Management Models, the Concepts and Definitions of Solid Waste and the Role of Municipalities in relation to the PNRS, the National Solid Waste Policy and the Final Destination Space for Solid Waste. The research is characterized as a multiple case study, of an exploratory, descriptive and qualitative nature, which consists of applying a structured interview to those responsible for solid waste management or the environmental area, containing 28 questions, totaling 20 (twenty) interviewed. The information was proven through discourse analysis and comparison of results against the obligations of the National Solid Waste Policy. The results stand out as the few existing actions in the municipalities, as well as the lack of knowledge of the law, making it clear that the cities are far from complying with the requirements of the law, and in only one municipality the actions are already in operation and more half of them only collect waste. Several difficulties were reported during the interviews: restrictions and resistance in the application of standards on the part of municipal governments, unpreparedness and lack of teams in the secretariats, non-adherence to programs on the part of citizens and lack of knowledge of the law on the part of secretaries and collaborators.